1996
DOI: 10.1088/0953-2048/9/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Transport critical current density above at 77 K in superconducting tapes made by the Ag wire-in-tube method

Abstract: Transport critical current density (J c ) is a limiting factor in the practical application of (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O y (BSCCO-2223) high-temperature superconducting materials. The minimum requirement is for a J c of 10 5 A cm −2 in long wires and tapes, at 77 K and in a high magnetic field. The issue of current distribution inside Ag-sheathed tapes has been resolved by showing that the region of high critical current density is next to the silver. In this paper we report a J c value > 10 5 A cm −2 at 77 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 14 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…By deconstructing tapes it was demonstrated that the thin layer of superconductor (about 10 µm) remaining on the silver sheath carried the same I c as did the intact tape [3]. These transport measurements resulted in a J c value greater than 10 5 A cm −2 at 77 K. Magnetization measurements on deconstructed tapes also confirmed the very high J c values in the thin layer of superconductor near the Ag sheath [4]. J c values greater than 10 6 A cm −2 were measured at 10 K. Tapes with a single Ag wire replacing the bulk of the central core of the superconductor were made [5].…”
Section: Introductionmentioning
confidence: 73%
“…By deconstructing tapes it was demonstrated that the thin layer of superconductor (about 10 µm) remaining on the silver sheath carried the same I c as did the intact tape [3]. These transport measurements resulted in a J c value greater than 10 5 A cm −2 at 77 K. Magnetization measurements on deconstructed tapes also confirmed the very high J c values in the thin layer of superconductor near the Ag sheath [4]. J c values greater than 10 6 A cm −2 were measured at 10 K. Tapes with a single Ag wire replacing the bulk of the central core of the superconductor were made [5].…”
Section: Introductionmentioning
confidence: 73%
“…The J c values for short pieces of SF tapes reflect an improvement by a factor of 2.9 in the last three years and they are 69 kA cm −2 [1,2] and 200 kA cm −2 [3] at 77 K and under the self-field. For technologically practical, MF long tapes (> 100 m) progress between 1992 and 1994 led to an improvement by a factor of 2.5, from > 10.5 kA cm −2 [4] to 26.5 kA cm −2 [5].…”
Section: Introductionmentioning
confidence: 84%
“…Existence of such a layer has been confirmed by microslice experiments [4], high-resolution transmission electron microscopy [SI, and magneto-optical imaging [6]. Based on these results and the ever increasing demand for conductors with high current transport properties, effort was made to develop superconducting tapes by the Ag wire-in-tube (WIT) method.…”
Section: P Haldarmentioning
confidence: 99%